How to Write Technical Reports Understandable Structure, Good Design, Convincing Presentation - Hering, Lutz.; Hering, Heike; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Writing technical reports" conveys the important and necessary knowledge of writing and presenting technical and scientific work. It answers typical questions about the formal layout and structure, typically arising during the writing process. In addition, it provides many tips ands tricks as well as examples from the real life. Thanks to it clear and easy writing, the book is perfectly suitable for autodidacts. This practical guide through technical writing is based on the fifth edition of very successful German book by the same authors.
Planning the Technical Report -- Writing and creating the Technical Report -- Useful behavior for working on your project and writing the Technical Report -- Presenting the Technical Report -- Summary.
Keywords: Engineering; Mathematics; Engineering; Engineering, general; Popular Science in Mathematics/Computer Science/Natural Science/Technology.